Perancangan Buku Cerita Legenda Tiongkok Air Mata Putri Meng Jiang - Jason Kristanto; Ayyub Anshari Sukmaraga (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2021)
Based on research, Indonesians have a low interest in reading books and there is still a representation of the Chinese generation's culture and also reducing the lessons of character toward children, so theres a need for Chinese folklore story book. The used story is